EFEKTIVITAS PROGRAM POSYANDU LANSIA DI DESA TAMBAK KALISOGO KECAMATAN JABON KABUPATEN SIDOARJO - Ari Nur Aliyah Rohalia; Hendra Sukmana (Journal Publicuho, 2024)
The following research aims to describe and analyze the effectiveness of the Elderly Posyandu Program in Tambak Kalisogo Village. This research uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The informants in this research were determined through purposive sampling, consisting of the Head of the Posyandu for the Elderly, the Village Treasurer, the Elderly Community, and the Head of Services as the person in charge of the Posyandu for the elderly program. The informant selection technique used in the following research is purposive sampling, namely technique. The data analysis model is carried out through the Miles Huberman analysis model (1984), namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the effectiveness of the elderly posyandu program in Tambak Kalisogo Village, Jabon District, Sidoarjo Regency is not optimal due to the lack of participation of elderly people in taking part in elderly posyandu activities. has not been implemented in its entirety. This means that the effectiveness of the elderly posyandu program in Tambak Kalisogo Village cannot be said to be effective.